2012
DOI: 10.1016/j.cell.2012.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Memory of Heterochromatin in Living Cells

Abstract: Summary Posttranslational histone modifications are important for gene regulation, yet the mode of propagation and the contribution to heritable gene expression states remains controversial. To address these questions, we developed a Chromatin in vivo (CiA) Assay system employing chemically-induced proximity to initiate and terminate chromatin modifications in living cells. We selectively recruited HP1α to induce H3K9me3-dependent gene silencing and describe the kinetics and extent of chromatin modifications a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

47
568
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 415 publications
(618 citation statements)
references
References 49 publications
47
568
2
1
Order By: Relevance
“…However, it does not preclude a role for chromocenters in active contribution gene repression. A hint that this may occur comes from the artificial recruitment of heterochromatin protein 1 variants (HP1) to a transgene, which was previously shown to cause increased association with chromocenters (Ayyanathan et al 2003) and to induce gene silencing (Ayyanathan et al 2003;Hathaway et al 2012). However, these experiments did not allow discerning whether the two effects were causally related: Silencing could have been induced by pericentromeric recruitment, but pericentromeric association may also have been the consequence of HP1-induced gene silencing (Ayyanathan et al 2003;Hathaway et al 2012).…”
Section: Induced Proximity To Chromocenters Is Sufficient For Transcrmentioning
confidence: 99%
“…However, it does not preclude a role for chromocenters in active contribution gene repression. A hint that this may occur comes from the artificial recruitment of heterochromatin protein 1 variants (HP1) to a transgene, which was previously shown to cause increased association with chromocenters (Ayyanathan et al 2003) and to induce gene silencing (Ayyanathan et al 2003;Hathaway et al 2012). However, these experiments did not allow discerning whether the two effects were causally related: Silencing could have been induced by pericentromeric recruitment, but pericentromeric association may also have been the consequence of HP1-induced gene silencing (Ayyanathan et al 2003;Hathaway et al 2012).…”
Section: Induced Proximity To Chromocenters Is Sufficient For Transcrmentioning
confidence: 99%
“…These domains also typically show peaked patterns of enrichment, rather than broad, flat plateaus (20). We recently showed that small-molecule-mediated recruitment of HP1α to the Oct4 (Pou5f1) locus gives rise to a symmetric and peaked H3K9me3 domain in both mouse ES cells and fibroblasts (20). This domain grew continuously over time to between 2 and 10 kbp while maintaining its peaked shape, allowing us to obtain kinetic measurements on the dynamics of H3K9me3 propagation in vivo.…”
mentioning
confidence: 99%
“…In mouse embryonic stem cells, the vast majority of noncentromeric H3K9me3 domains span less than 10 kbp, with most less than 5 kbp (18,19). These domains also typically show peaked patterns of enrichment, rather than broad, flat plateaus (20). We recently showed that small-molecule-mediated recruitment of HP1α to the Oct4 (Pou5f1) locus gives rise to a symmetric and peaked H3K9me3 domain in both mouse ES cells and fibroblasts (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acetylation events are measured in the order of minutes, while methylation events are stable for days (Barth and Imhof, 2010). These rate differences are determined by the enzymes that catalyze the corresponding reactions (Hathaway et al, 2012). A given mark can be removed either by specific de-modification enzymes or through chromatin remodeling (e.g., histone turnover or histone tail clipping).…”
Section: H4k20me H4k20mementioning
confidence: 99%